Implementation study of an intermediate medication review in Belgian community pharmacies - Lelubre, M.; Wuyst, J.; Maesschalck, J.; Duquet, N.; Foubert, K.; Hutsebaut, C.; Moullin, Joanna; De Wulf, I.; Boussery, K.; Foulon, V.; De Vriese, C. (Elsevier, 2018)
© 2018 Background: The Association of Pharmacists in Belgium (APB) and local pharmacy associations launched a pilot project in collaboration with research teams from three Belgian universities to study the impact and implementation-related issues of a medication review (MR) service type 2a in Belgian community pharmacies. Objective: The aim of this paper is to describe the implementation process of the MR service and to present the implementation evaluation of the pilot study (testing stage). Methods: The pilot project was a prospective observational study using mixed methods. The implementation evaluation was based on the RE-AIM model and the framework for the implementation of services in pharmacy (FISpH). Collected implementation outcomes were classified into four dimensions: reach, adoption, implementation and intent of maintenance. Results: During the testing stage, 80 pharmacies participated in the study, but 25 dropped out (31%), mainly because of a reported lack of time (adoption). The 55 remaining pharmacies included 457 patients. Recruiting patients into the service was challenging for pharmacists as 48.5% of patients refused the pharmacists’ proposal (reach). Internal organizational factors were major barriers for pharmacists, followed by the lack of adoption by the pharmacy team. Large pharmacies in which pharmacy owner led the project were observed to be more proactive in implementing the MR service by integrating organizational strategies to assist the implementation process (implementation). Interviewed pharmacists perceived this new service as a professionally satisfying activity. Among participating pharmacists, 92.5% found this service feasible in practice, but believed it required adapted resources to reorganize the internal pharmacy workload, additional support, such as broad-based media campaigns to increase physicians’ and patients’ awareness and attitudes towards the service, and modified software (maintenance). Conclusions: The medication review service was implemented in 68% of participating pilot Belgian community pharmacies but would require adapted resources and supports for larger scale implementation.